Bridging Theory and Practice: University Extension and Community Engagement in the Rondon Project (Global Journal of Human-Social Science, 2025)
The Rondon Project an initiative by the Brazilian Federal Government in collaboration with Higher Education Institutions promotes actions to foster the development of cities and communities across Brazil The project aims to support local and sustainable development and enhance citizenship among participants through socially focused projects Key objectives include contributing to the civic education of university students integrating them into national development through participatory actions and fostering a sense of social responsibility toward citizenship development and national interests The Federal University of Ouro Preto sent a team of 8 students and 2 professors to Japonvar Minas Gerais Brazil This report focuses on workshops from the Labor axis Methodologies included multimedia presentations discussion circles interactive activities music posters and flyers aimed at creating knowledge multipliers The actions developed significantly contributed to the economic development and quality of life of the population involved in the operation
Keywords: rondon project; university extension; community development; social responsibility; knowledge multipliers